PENGARUH PRINSIP GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN (STUDI PADA PT. BANK RAKYAT INDONESIA Tbk. CABANG BUMI SERPONG DAMAI KOTA TANGERANG) - Cahya, Bernardinus Adi (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to determine the effect of the implementation of Good Corporate Governance principles, which consists of transparency, accountability, responsibility, independency, and fairness, on the financial performance of PT. Bank Rakyat Indonesia Tbk. Branch of Bumi Serpong Damai in Tangerang City. This study uses data obtained from questionnaires and direct observation. Using random sampling method, this study has selected 52 employees of PT. Bank Rakyat Indonesia Tbk Branch of Bumi Serpong Damai in Tangerang City as the respondents. The hypothesis of this research is assessed using multiple regression analysis. This study finds that the implementation of responsibility principle improves the financial performance of the company. However, transparency, accountability, independency, and fairness do not affect the company’s financial performance.Keywords : good corporate governance principle, financial performance